Does inclusion of education and marital status improve SCORE performance in central and eastern europe and former soviet union? findings from MONICA and HAPIEE cohorts - Vikhireva, Olga; Broda, Grazyna; Kubinova, Ruzena; Malyutina, Sofia; Pająk, Andrzej; Tamosiunas, Abdonas; Skodova, Zdena; Simonova, Galina; Bobak, Martin; Pikhart, Hynek (PloS one, 2014)
BACKGROUND AND OBJECTIVE: The SCORE scale predicts the 10-year risk of fatal atherosclerotic cardiovascular disease (CVD), based on conventional risk factors. The high-risk version of SCORE is recommended for Central and Eastern Europe and former Soviet Union (CEE/FSU), due to high CVD mortality rates in these countries. Given the pronounced social gradient in cardiovascular mortality in the region, it is important to consider social factors in the CVD risk prediction. We investigated whether adding education and marital status to SCORE benefits its prognostic performance in two sets of population-based CEE/FSU cohorts. METHODS: The WHO MONICA (MONItoring of trends and determinants in CArdiovascular disease) cohorts from the Czech Republic, Poland (Warsaw and Tarnobrzeg), Lithuania (Kaunas), and Russia (Novosibirsk) were followed from the mid-1980s (577 atherosclerotic CVD deaths among 14,969 participants with non-missing data). The HAPIEE (Health, Alcohol, and Psychosocial factors In Eastern Europe) study follows Czech, Polish (Krakow), and Russian (Novosibirsk) cohorts from 2002-05 (395 atherosclerotic CVD deaths in 19,900 individuals with non-missing data). RESULTS: In MONICA and HAPIEE, the high-risk SCORE ≥5% at baseline strongly and significantly predicted fatal CVD both before and after adjustment for education and marital status. After controlling for SCORE, lower education and non-married status were significantly associated with CVD mortality in some samples. SCORE extension by these additional risk factors only slightly improved indices of calibration and discrimination (integrated discrimination improvement <5% in men and ≤1% in women). CONCLUSION: Extending SCORE by education and marital status failed to substantially improve its prognostic performance in population-based CEE/FSU cohorts.
Keywords: senioři; Russia; senioři nad 80 let; Prognosis; Socioeconomic Factors; Cohort Studies; Europe, Eastern; Rusko; Middle Aged; mužské pohlaví; ateroskleróza; Adult; Atherosclerosis; kohortové studie; Marital Status; východní Evropa; socioekonomické faktory; Aged, 80 and over; Cardiovascular Diseases; ženské pohlaví; prognóza; Humans; manželský stav; lidé středního věku; rizikové faktory; dospělí; Female; Aged; Risk Factors; kardiovaskulární nemoci; lidé; Male